Environmental determinants of the taxonomic and functional alpha and beta diversity of small mammals in forest fragments in southwestern Amazonia, Brazil - André L.M. Botelho; Rosana Gentile; Cibele R. Bonvicino; Charle F. Crisóstomo; Marcos Silveira; Paulo S. D’Andrea (Global Ecology and Conservation, 2025)
Environmental factors can alter the relative importance of deterministic and stochastic processes as determinants of community structures. Understanding community-level landscape patterns subject to shifts in land use is essential for developing effective conservation measures. The present study investigated the environmental factors, such as fragment and matrix characteristics, that influence the taxonomic and functional diversity (alpha and beta) of small nonvolant mammals in 10 forest fragments in southwestern Amazonia. Specimens were captured using a combination of pitfalls and cage traps, set on the ground and in the understorey. In total, 285 specimens, representing 22 species were captured. Richness was positively influenced by fragment size, whereas species diversity (Hill’s q=1) was positively influenced by bamboo cover. Functional diversity was related to matrix quality, although the null model was also selected. The functional species composition was primarily related to fragment size, matrix quality, and degree of fragmentation of the matrix. Both taxonomic and functional beta diversity were significantly correlated with fragment size and matrix quality. The alpha and beta diversity patterns recorded here reinforce the importance of deterministic processes, particularly fragment size and matrix quality, as drivers of the structure of communities of small mammals in fragmented landscapes.